2014
DOI: 10.1007/s00429-014-0833-6
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent structural plasticity of Purkinje cell spines in cerebellar vermis and hemisphere

Abstract: The environmental enrichment (EE) paradigm is widely used to study experience-dependent brain plasticity. In spite of a long history of research, the EE influence on neuronal morphology has not yet been described in relation to the different regions of the cerebellum. Thus, aim of the present study was to characterize the EE effects on density and size of dendritic spines of Purkinje cell proximal and distal compartments in cerebellar vermian and hemispherical regions. Male Wistar rats were housed in an enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 95 publications
(105 reference statements)
3
23
0
Order By: Relevance
“…Previous studies on the effects of EE on structural plasticity refer mainly to spine density and dendritic tree complexity (Berardi et al, 2015;De Bartolo, Florenzano, Burello, Gelfo, & Petrosini, 2015;Leggio et al, 2005). Here, we demonstrate that EE also affects structural plasticity of the AIS.…”
Section: Area V2supporting
confidence: 61%
See 1 more Smart Citation
“…Previous studies on the effects of EE on structural plasticity refer mainly to spine density and dendritic tree complexity (Berardi et al, 2015;De Bartolo, Florenzano, Burello, Gelfo, & Petrosini, 2015;Leggio et al, 2005). Here, we demonstrate that EE also affects structural plasticity of the AIS.…”
Section: Area V2supporting
confidence: 61%
“…The positive beneficial effects of EE on brain synaptic plasticity and behavior have been known for decades (Berardi et al, ). Previous studies on the effects of EE on structural plasticity refer mainly to spine density and dendritic tree complexity (Berardi et al, ; De Bartolo, Florenzano, Burello, Gelfo, & Petrosini, ; Leggio et al, ). Here, we demonstrate that EE also affects structural plasticity of the AIS.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether EE, a more natural brain stimulating paradigm involving motor skill acquisition, can also produce PF MSBs in the cerebellar cortex of mice, we estimated synaptic density in a series of consecutive electron microscopic images using the physical disector method. Consistent with a recent study (De Bartolo et al, ), we found a significant increase in the number of PF‐to‐Purkinje cell synapses per unit volume in enriched mice compared to control animals (Control, 0.63 ± 0.02/μm 3 ; EE, 0.83 ± 0.02/μm 3 ; Student t ‐test, p < .0001, n = 5 animals per group) (Figure c). PF‐to‐Purkinje cell synapses were further classified as SSBs contacting only one spine and MSBs contacting more than two spines.…”
Section: Resultssupporting
confidence: 91%
“…Animals were maintained at room temperature and humidity with a 12‐h light: 12‐h dark cycle. The EE group was housed with wheels, tunnels, plastic tires, platforms, and wooden toy houses, according to the procedure specified in the previous report (De Bartolo et al, ) with a slight modification (Figure b). All animal experiments are in compliance with the guidelines for Korea University Institutional Animal Care & Use Committee (KUIACUC‐2011‐222).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation